An efficient high performance reconfigurable canonical sign digit architecture for software defined radio - Chalampalem, Vijaya Bhaskar; Pidugu, Munaswamy (International Journal of Reconfigurable and Embedded Systems (IJRES), 2024)
Software defined radios (SDRs) are highly motivated for wireless device modelling due to their flexibility and scalability over alternative wireless design options. The evolutionary structure of finite impulse response (FIR) filters was designed for a proposed reconfigurable canonical sign digit (CSD) approach. Considering the complex trade-off, this is accomplished with many FIR taps, which is a challenging assignment. On the baseband processing side, design is given with parameterization-controlled FIR filter tap selection. Optimal processing models to overcome the reconfigurable design issues associated with the SDR system for a multi-standard wireless communication system root cosine filter standard are often used to implement multiple FIR channelization topologies, each of which is tied to a particular in-phase and quadrature (IQ) symbol. Additionally, it demonstrates the viability of using a multi-modulation baseband modulator in the SDR system for next-generation wireless communication systems to maximise adaptability with the least amount of computational complexity overhead. The proposed multiplier-less FIR filter-based reconfigurable baseband modulator, according to the experimental results, offers a 6% complexity reduction and a 47% improvement in performance efficiency over the current SDR system.